The Covid 19 Pandemic Impact on Micro, Small and Medium Sized Enterprises Policy - United Nations Conference on Trade; Development (United Nations, 2022)
Competition and market access challenges are being faced by Micro, Small and Medium-sized Enterprises (MSMEs) around the world as they seek to deal with the impact of COVID-19 on their operations. This publication is prepared within the Development Account project on COVID 19 and the resurgence of SMEs.